Strategi Meningkatkan Mutu Pendidikan Melalui Manajemen Sarana dan Prasarana di SMA Negeri 3 Tebing Tinggi Kabupaten Empat Lawang Provinsi Sumatera Selatan - Wira Alvio (Madani: Jurnal Ilmiah Multidisiplin, 2022)
This study aims to reveal strategies to improve the quality of education through the management of facilities and infrastructure at SMA Negeri 3 Tebing Tinggi with a focus on: 1) Planning for facilities and infrastructure at SMA Negeri 3 Tebing Tinggi, 2) Use of facilities and infrastructure at SMA Negeri 3 Tebing Tinggi, 3) Supervision of facilities and infrastructure at SMA Negeri 3 Tebing Tinggi, 4) Reporting on facilities and infrastructure at SMA Negeri 3 Tebing Tinggi, 5) Obstacles faced in facilities and infrastructure at SMA Negeri 3 Tebing Tinggi. This research method uses descriptive qualitative through interviews, which describes the strategy to improve the quality of education through the management of facilities and infrastructure in SMA Negeri 3 Tebing Tinggi in improving the management of facilities and infrastructure. The results of the study show that: 1) Planning for the procurement of facilities and infrastructure programs has been made by the student section to develop facilities in activities at school, 2) The use of facilities and infrastructure is carried out according to the learning needs of each teacher and is regulated and monitored in an orderly manner, 3) Supervision of facilities and infrastructure has been carried out directly by the school principal, 4) Reporting has been carried out every year, namely at the beginning of the school year submitted to the Education Office, 5) Obstacles faced in facilities and infrastructure are financing both for procurement and maintenance. Based on the research results, it is suggested the following: 1) The principal is expected to optimize supervision of all planned activities so that the predetermined goals can be achieved. 2) It is necessary to involve the government, local government and the community in procuring financing and maintaining facilities and infrastructure. 3) Teachers, administrators are expected to be involved in the management of facilities and infrastructure.